Methods of Promoting Narrative Skills in Children With Insufficient Development of Language System - Tūbele, Sarmīte; Cupere, Irina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This article explores the issue of promoting storytelling skills in preschool children with insufficient development of language system, such as making retellings, narrative stories, stories based on plot pictures and the problems faced by children drawing up short stories. There are presented also the methodological aspects of speech therapist’s activities when working with such children and promoting narrative skills and abilities to tell stories. Methods of game, modeling, mnemonics and drawing with comments are described